Lay of the land: narrative synthesis of tackle research in rugby union and rugby sevens. Issue 1 (19th April 2020) - Burger, Nicholas; Lambert, Mike; Hendricks, Sharief
Abstract : Objectives: The purpose of this review was to synthesise both injury prevention and performance tackle-related research to provide rugby stakeholders with information on tackle injury epidemiology, including tackle injury risk factors and performance determinants, and to discuss potential preventative measures. Design: Systematic review and narrative synthesis. Data sources: PubMed, Scopus and Web of Science. Eligibility criteria: Limited to peer-reviewed English-only publications between January 1995 and October 2018. Results: A total of 317 studies were identified, with 177 in rugby union and 13 were in rugby sevens. The tackle accounted for more than 50% of all injuries in rugby union and rugby sevens, both at the professional level and at the lower levels, with the rate of tackle injuries higher at the professional level (mean 32/1000 player-hours) compared with the lower levels (mean 17/1000 player-hours). A player's tackle actions and technical ability were identified as major risk factors for injury and a key determinant of performance. Summary/conclusion: Evidence-based education, progressive tackle technique training with a high potential to transfer and law changes have been proposed as key modifiers of player tackle actions and technical ability. Conceivably, all three modifiers working in unison (as opposed to separately) will have a higher potential at reducing tackle injury risk while enhancing performance. With the guidance of tackle injury and performance studies, as well as stakeholder engagement, experiential and explorative tackle research has the potential to inspire innovative injury prevention and performance strategies.